Neutron star cooling (2006)
The subject of Neutron Star Cooling is discussed. First, some general properties of neutron stars are treated in order to put the problem of Neutron star cooling in context. Cooling curves of isolated Neutron stars undergoing neutrino emission are calculated, and are finally compared with actual observed temperatures.